Working Tenure as One of the Factor Associated with Stigma towards Healthcare Practitioners during Pandemic - Theresia, Theresia; Manik, Marisa; Natalia, Siska (Fakultas Ilmu Kesehatan Universitas Dharmas Indonesia, 2024)
Background: Healthcare practitioners faced psychological challenges, including stigmatization, during the COVID-19 pandemic. Both healthcare practitioners and the general population experienced stigma due to uncertainty. Aim: To understand factors associated with social stigma towards healthcare practitioners caring for COVID-19 patients. Method: A sequential mixed methods study was conducted. Quantitative data were collected first through an online survey distributed via WhatsApp to nursing directors at private hospitals, using the Indonesian version of the stigma scale. A total of 195 healthcare professionals (184 medical, 9 non-medical) participated. High-stigma participants were interviewed. Data were analyzed using descriptive statistics, ANOVA, and hierarchical regression. Thematic analysis was used for qualitative data. Results: Participants included nurses (84.5%), midwives (5.2%), doctors (5.7%), and non-medical professionals (4.6%). Probable COVID-19 status positively correlated with profession type (r=0.144, p<0.047). Stigma scores negatively correlated with COVID-19 testing type (r=-0.147, p<0.042) and working tenure (r=-0.147, p<0.041). Hierarchical regression showed that working tenure, probable status, and testing type predicted stigma. Profession type and confirmed cases did not predict stigma. Qualitative findings indicated junior nurses (1-2 years tenure) experienced stigma, especially when visiting testing facilities and having probable status. The negative correlation between tenure and stigma was consistent in qualitative data. Conclusions: Working tenure, probable COVID-19 status, and testing type are associated with stigma among healthcare practitioners. Recommendation: Future studies should use more rigorous designs and validated COVID-19-specific tools.